The variable UV central spike of NGC 4552 - Cappellari, M; Burstein, D; Buson, L; Alighieri, S; Greggio, L; Renzini, A; Funes, J; Bertola, F (1997)
The nature of the UV-bright spike at the center of the otherwise normal galaxy NGC 4552 is investigated by means of both Hubble Space Telescope (HST) imaging (FOC) and spectroscopy (FOS). This central feature-which underwent a recent dramatic UV flare-provides a potential new tool for revealing the presence of massive black holes in normal galaxies. In particular the sub-arcsec FOS spectra of the nucleus suggest that NGC 4552 does harbor an object with mass M > 4 x 10(8) M. within the central 2 pc.